Implementation of The School Budget Activity Plan Application (Arkas) And The Bos Fund Management Information System On The Accountability Of Bos Financial Reporting In Education Entities In Cirebon City - Mohammad Syarif; Irwan Sutirman Wahdiat (PT. Publikasiku Academic Solution, 2024)
The purpose of this study was to analyse the effect of the School Budget Activity Plan (ARKAS) application and the BOS Management Information System (SIMBOS) application on the accountability of financial reporting of BOS funds in elementary schools in Cirebon City. We conducted this research using quantitative methods. We distributed questionnaires as part of the data collection technique. Furthermore, we will conduct validity and reliability tests on the responses to these questionnaires. We carried out the data analysis using linear regression. This research findings that the use of the School Budget Work Plan (ARKAS) application significantly influences the accountability of BOS fund use in elementary schools in Cirebon City, with better use of the ARKAS application leading to more transparent use of BOS funds. The BOS Management Information System (SIMBOS) also has a significant effect on the transparency of the use of BOS funds in public elementary schools in Cirebon City. The better the use of the ARKAS application, the more transparent the use of BOS funds.